DDR1 (Discoidin Domain Receptor-1)-RhoA (Ras Homolog Family Member A) Axis Senses Matrix Stiffness to Promote Vascular Calcification - Ngai, David (Arterioscler Thromb Vasc Biol, 2020)
OBJECTIVE: Vascular calcification is a pathology characterized by arterial mineralization, which is a common late-term complication of atherosclerosis that independently increases the risk of adverse cardiovascular events by fourfold. A major source of calcifying cells is transdifferentiating vascular smooth muscle cells (VSMCs). Previous studies showed that deletion of the collagen-binding receptor, DDR1 (discoidin domain receptor-1), attenuated VSMC calcification. Increased matrix stiffness drives osteogenesis, and DDR1 has been implicated in stiffness sensing in other cell types; however, the role of DDR1 as a mechanosensor in VSMCs has not been investigated. Here, we test the hypothesis that DDR1 senses increased matrix stiffness and promotes VSMC transdifferentiation and calcification. APPROACH AND RESULTS: Primary VSMCs isolated from Ddr1(+/+) (wild-type) and Ddr1(−/−) (knockout) mice were studied on collagen-I–coated silicon substrates of varying stiffness, culturing in normal or calcifying medium. DDR1 expression and phosphorylation increased with increasing stiffness, as did in vitro calcification, nuclear localization of Runx2 (Runt-related transcription factor 2), and expression of other osteochondrocytic markers. By contrast, DDR1 deficient VSMCs were not responsive to stiffness and did not undergo transdifferentiation. DDR1 regulated stress fiber formation and RhoA (ras homolog family member A) activation through the RhoGEF (rho guanine nucleotide exchange factor), Vav2. Inhibition of actomyosin contractility reduced Runx2 activation and attenuated in vitro calcification in wild-type VSMCs. Finally, a novel positive feedforward loop was uncovered between DDR1 and actomyosin contractility, important in regulating DDR1 expression, clustering, and activation. CONCLUSIONS: This study provides mechanistic insights into DDR1 mechanosignaling and shows that DDR1 activity and actomyosin contractility are interdependent in mediating stiffness-dependent increases in VSMC calcification.